The Effect of Using Exercises With Aids for Teaching Types of Shooting To Sophomore Students - Mohameed, Alaa (Journal of Physical Education, 2017)
Handball gained a lot of interest by researchers all over the world. The problemof the research lies in weakness in performing some shooting skill in handball. Theresearcher used the experimental method. The subjects were (19) sophomore students ofphysical education and sport sciences college/ University of Baghdad of the academic year2015 – 2016. The research aimed at identifying the effect of these exercises using aids forteaching some types of shooting in handball. The researcher conclude the positive effects ofthe proposed exercises on some types of shooting. Finally the researcher recommended thenecessity of using aids for teaching shooting in sophomore stuetns of physical edcaution andon other grades.